Oximetry response in individuals exposed to intermittent normombaric hypoxia - Norris, S. R.; KoIb, J.; Neil, R.; Smith, D. J. (2001)
This investigation examined pulse oximetry responses (SpO2) to a period of intermittent normobaric hypoxia (Hypoxico, mc) exposure in twelve healthy and active male volunteer subjects (28±10 yr). The project required five consecutive 12 hour exposures (overnight; typically, 19:00 to 07:00 hr) to a simulated altitude of approximately 4000 m (Calgary; approx. 1000 m elevation). Near-infrared pulse oximetry devices (Nellcor NPB-295), capable of frequent memory storage and computer downloadable, were attached to each subject upon entry into the hypoxic environment using a malleable finger sensor. The SpO2 and %02 information, averaged over each hour of each exposure, was then examined using a 2-way MANOVA (a priori = 0.05), followed by a Scheff~ post-hoc procedure where appropriate. The two dependent variables were examined against 'night' and 'hour' of hypoxic exposure. A significant main effect for both night and hour was observed (p<O.O5), with no interaction between these components. In specific reference to SpO2, the average of the first night of exposure was significantly lower than the other four nights (85.1 vs. 87.9, 88.3, 89.3 and 89.0%, respectively), with all other combinations being insignificant. The average %02 in each hypoxic setting for each night and hour yielded no significant differences (14.34, 14.28, 14.32, 14.28 and 14.42%, respectively). The 'by hour' comparisons for SpO2 revealed that the first hour of each exposure was significantly higher than the following hours (pKO.05). indicative of the time taken to stabilize the environment and the subject. A consistency of SpO2 was then typically observed from hour #3 to hour #10, with a trend towards an increasing SpO2 over the final two hours of each exposure. It is clear from these results that SpO) may be used as a simple measure with which to describe accommodation to an intermittent hypoxic environment. Supported by the ('algaty Olympic Development Association (CODA).